On the concept of safety instrumented systems - Barrero Páez, Luis Efrén; Escobar Díaz, Andrés; Vacca González, Harold (Visión electrónica, 2014)
This paper presents a concrete definition of what a Safety Instrumented System (SIS) is. This involves important concepts such as risk, safety integrity level, SIL, life cycle and protection layer. The aim of this paper is to provide readers with a concise definition of SIS. To this end, the basic elements of a SIS are defined, the relationship of risk with a SIS is presented, layers of protection are defined in a industrial process, the implementation of a SIS is justified, and the correct methodology for the implementation of a SIS is obtained, namely Lifecycle. Finally, the paper describes a mathematical method for modeling and validating a particular SIS based on standards.